Monitoring self-reported basic emotions related to Covid-19 confinement and return to everyday life - Maya Pérez, Eloy (2020)
Emotions are a central element for understanding the human experience. With the intention of paying for this understanding, the present study was designed aimed at the analysis of the basic emotions related to confinement by covid-19 and with the return to daily life. For which a survey with 21 items was developed, 230 people participated, of which 73.2% were women and 26.4% men, with ages ranging between 22 and 71 years, the central characteristic for the choice of said participants was who will be working before and in the months after the declaration of confinement in Mexico. The results describe the existence of negative emotions associated with the participants' self-perception; especially fear as the emotion that manifested the most (f = 117), followed by sadness and anger. It is concluded that in relation to the psychological principle of emotional addition there is a negative tendency towards experienced affects.